Governance, Policy and Juxtaposition - Roe, Michael. author. aut Link
XVI, 343 p.
Keywords: This book considers governance and policy-making within the maritime sector, and focuses significantly on the dimensional context within which governance works. Recognising the importance of understanding governance and policy at times when the world is faced with social, political, and economic problems, it highlights the fact that both areas are equally significant in understanding today’s political economy. By focusing on the maritime sector, a pillar industry supporting international trade activities, the book offers a unique perspective to explain the difficulties of balancing policy-making with governance in order to provide solutions. It also examines the importance of developing a governance process that encourages and accommodates juxtaposition in a way that ensures that the effect of independent policy-making is understood upon the success or otherwise of policies across a range of contexts and problems. Given the in-depth nature of the text, it is of interest to academics, researchers and professionals in the field. .